If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 1 = 107 + -3x Reorder the terms: 1 + 9x = 107 + -3x Solving 1 + 9x = 107 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 1 + 9x + 3x = 107 + -3x + 3x Combine like terms: 9x + 3x = 12x 1 + 12x = 107 + -3x + 3x Combine like terms: -3x + 3x = 0 1 + 12x = 107 + 0 1 + 12x = 107 Add '-1' to each side of the equation. 1 + -1 + 12x = 107 + -1 Combine like terms: 1 + -1 = 0 0 + 12x = 107 + -1 12x = 107 + -1 Combine like terms: 107 + -1 = 106 12x = 106 Divide each side by '12'. x = 8.833333333 Simplifying x = 8.833333333
| x=(4x+3)(2x+1) | | -1.24*-4= | | 12x=5+2x | | 5x+9+4x=3+8x | | 10s+5t=65 | | (4x/3)-x=(x/15)-(16/15) | | 9x-103=4 | | 10x-48=32 | | 154=16-4n | | 154-5n=16+n | | 35/3x-1=7 | | 10t^2-2t^3-4t^4= | | 6.27+2.09*3= | | 6.27*2= | | 3(6.27+2.09)= | | 3(x+2.09)=2x | | 2x+3y+x-5y= | | 2x+3y+x-5= | | -7(3)= | | -5(x+2)-11=13+6 | | 3x(x-2)=4 | | x-2a=x-2b | | x-2a=x-cb | | 56*0.9+x*0.1=60 | | x+9=-3+11 | | x^2-15+24=-2x-18 | | -3=r/4-5 | | -100=-9+7x | | 8=7+k/12 | | 10+n/1=10 | | 8+6x=-112 | | -5+4n=63 |